ANALISIS PENGARUH ZAKAT, INFAK, SEDEKAH DAN USYR (PAJAK IMPOR) TERHADAP KEMISKINAN DI INDONESIA - Eka RatnaSari; Firdayetti Firdayetti (Media Ekonomi, 2018)
This research discussed the analysis affecting zakat, donation, alms and users (import tax) to the proverty in Indonesia. The method used in the study is a multiple regression method with classical assumptions. The data used in this study is secondry data and time series data used. the year of this study began from 2001-2016. The results using multiple regression analysis, it appears that the zakat variabel significantly affect to the reduction of poverty, infak and sedekah variabel, and usyr (import tax) variabel not significantly affect to the reduction of poverty and have adjusted R-square is nice.